Challenge - silence kills: social media and information in the fight against violence against women (Research, Society and Development, 2021)
Objective: to report the experience regarding the use of a Digital Information and Communication Technology as a measure to prevent and combat violence against women, which intensified during the period of the COVID-19 pandemic, during social isolation. Methodology: this qualitative scientific production corresponds to an experience report, whose purpose is to expose the process of creation and implementation of an interventionist technology, during the period from February to June of 2020, the result of an intervention project against violence practiced against women. Results: the "Challenge: silence kills" exposes the main reporting channels that are available to the victim and third parties, and proved to be effective in encouraging the abuser to complain to the perpetrator, as well as people who witness the violent cases, having significant repercussions. Conclusion: Violence against women is a topic that, despite being much discussed, still needs to be explored through tools that are capable of impacting the general public. Thus, the proposal of the work was to expose alarming data on the rates of aggression practiced against women and its increase in the period of social isolation, encouraging not only debates on the subject, but also denunciation of cases.